Phalangeal Fractures- Management by Cost Effective Syringe Fixators - Jehanzaib Shah, ObaidurRahman, Riaz Ahmad, Muhammad Ali Bashir, Imtiaz Shakir, Aamir Munir, Rana Muhammad Adnan (Journal of Rawalpindi Medical College, 2015)
Background : To investigate the effectiveness of a locally developed, economical and simple fixator in the management of complex phalangeal fractures of the hand. Methods: In this descriptive study of twenty patients, suffering from simple or complex phalangeal fractures, two K wires(size1.6-2mm) and an empty syringe barrels (3cc,5cc or 10 cc) were used. K wire was first passed through the barrel. Then the K wire with the barrel was inserted into the site proximal to the fracture just lateral to the central slip of extensor tendon. A second K wire was passed into the site distal to the fracture site while holding the finger in traction and reduction. The reduction was checked under image and if not satisfactory the pins were inserted again after appropriate reduction. The patients were recalled after 3 weeks. Patients with restricted joint motion were advised aggressive physiotherapy. Patients were again reviewed at the end of 8 weeks. Results were analyzed by Belsky’s criteria and were graded as excellent (pain-free union/no deformity/total active motion (TAM) > 215°, good (pain-free union/ minimal deformity/ TAM > 180°) and poor ( pain or non-union/ deformity affecting function or cosmesis/ TAM <180°0.Total active motion (TAM) means cumulative active range of motion of one digit i.e. of metacarpo phalangeal joint and two interphalangeal joints. Gingrass criteria were used for assessment of thumb injuries and were graded as excellent(palmar abduction (PAB) > 45°/ total flexion (TF) >100°), good ( PAB >30°/ TF >75°) and poor- PAB < 30°/ TF < 75°).6 If sufficient callus was seen on X- rays the syringe fixator was removed on OPD basis. Results: All patients were male. Mean age was 32 ±10 years. Fourteen patients sustained injury to their left hand while 6 patients had their right hand injured. Commonest site was proximal phalanx(70%).Fractures healed at 3-4 weeks. Two patients with open fracture developed infection. Using Belsky’s criteria 30% patients exhibited excellent results and 60 % showed good results . Pain free union was obtained in 75% Eight patients (42%) healed without deformity. Total active motion (TAM) was ≥ 2000 in 8 patients (40%), between 180-200o in 10 patients (50%) and 170o in 2 patients (10%). Conclusion: This easy technique of external fixation using readily available and cheap items in treating open fractures of the fingers is effective in maintaining acceptable degree of hand function as well as hand cosmesis